An Interdisciplinary Study between Arabic Language Teaching and English Language Teaching on the Attitudes toward Learning Foreign Languages - Ahmet Erdost Yastibaş; Celal Turgut Koç (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
The present study aimed to find out the attitudes of Arabic as a foreign language (AFL) and English as a foreign language (EFL) students toward learning foreign languages in the Turkish higher education context within an interdisciplinary perspective. It was designed as a survey study and conducted with 26 Turkish AFL students and 26 Turkish EFL students who were chosen through convenience sampling. The data were collected through the attitude toward learning foreign languages scale for students studying at schools of Foreign Languages and were analyzed with descriptive statistics. According to the findings of the present study, the opinions of the participants related to foreign language lessons and their emotions related to learning foreign languages were positive, while their opinions about learning foreign languages were not very negative. Also, the findings indicated that the participants gave a lot of importance to learning foreign languages and used foreign languages on social media a lot. As a result of these, the findings revealed that both participant AFL and EFL students had a positive attitude toward learning foreign languages. The findings were discussed. The implications and limitations of the present study were explained, and suggestions for future studies were made.